A rule for group decision - Morkeliūnas, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. И. Моркелюнас. Одно правило группового решения A. Morkeliūnas. Viena grupinio sprendimo taisyklė